Photoprotective Potential, Cytotoxicity, and UPLC-QTOF/MS Analysis on Bioactive Solvent Fractions of Moringa concanensis Nimmo Bark. (23rd April 2022) - Santhanam, Rameshkumar; Karunakaran, Thiruventhan; Sowndhararajan, Kandhasamy; Zulkifli, Muhammad Faiz; Govindan Kothandaraman, Mouriya; Aravindhan, Veerasamy; Wan Ismail, Wan Iryani
Abstract : Moringa concanensis Nimmo (Moringaceae) belongs to the same family of M. oleifera (miracle tree) and is a medicinal plant traditionally used by Indians to treat various ailments related to diabetes, tumours, inflammation, and blood pressure. Despite its versatility, the photoprotective properties of the plant remain unclear . This study revealed the UV-protective properties of its methanol bark extract and respective subfractions, chloroform, hexane, and ethyl acetate through total phenolic and flavonoid content (TPC & TFC), antioxidant (DPPH), sun protecting factor (SPF) value, and UV absorption spectra analysis. This study also investigated on the inhibitory effect of the tested samples on collagenases and elastase, which are well-known for their role in the skin. The cytotoxic and H2 O2 scavenging properties of M. concanensis in 3T3-L1 cells were explored. Finally, the phytochemical profiling of the active fraction was conducted through UPLC-QTOF/MS analysis. Among the tested fractions, the chloroform fraction of M. concanensis showed the highest TPC (30.92 ± 0.71 mg GAE/DW), TFC (29.05 ± 0.09 mg QE/DW), and antioxidant properties (IC50 -6.616 ± 1.90 μ gml −1 ). Additionally, chloroform fraction demonstrated the highest SPF value, 10.46 at 200 μ gml −1, compared to the other tested fractions. All the fractions showed a broad absorption spectrum covering both UVA and UVB ranges. The chloroform fraction of M. concanensis also showed collagenase (50%) and elastase (IC50 -2.95 ± 1.23 μ gml −1 ) inhibition properties similar to the positive control. Cytotoxic results revealed that the chloroform fraction of M. concanensis prevented the H2 O2 -induced oxidative damage in 3T3-L1 cells even at lower concentrations (1.56 μ gml −1 ). UPLC-QTOF/MS analysis tentatively identified the presence of bioactive flavonoids and phenolics such as astragalin, quercetin, isoquercetin, and caffeic acid in the active fraction of M. concanensis bark. Overall, it is suggested that the chloroform fraction of M. concanensis bark has the potency to be used as an active ingredient in sunscreen products.